SARS-CoV-2: mental health of nurses who work on the frontline in a federal hospital in Rio de Janeiro - Guimarães, Anna Caroline Villela (2022)
Introduction: Studies on the mechanism of action and transmissibility of the SARS-CoV-2 virus reveal that we live in a period of propagation of modified strains. In the midst of this scenario, different professional categories, such as nurses, are on the front line of care and are directly involved in situations that can compromise mental health. in the units intended for the semi-intensive and intensive treatment of the contaminated population. Objectives: To identify factors related to the mental health of nurses who are on the front line at a Federal Hospital in Rio de Janeiro in the context of the pandemic caused by SARS-CoV-2. intensive care of people contaminated by the SARS-CoV-2 virus. Methodology: This is an exploratory and descriptive field research, with a qualitative approach, carried out with 17 nurses from the trauma, intensive care and COVID wards of a Federal Hospital in Rio de Janeiro who work on the front line of care for the population contaminated by the SARS-CoV-2 virus. Semi-structured interviews and thematic content analysis of the reports were carried out on how they understood their mental health in the context of the pandemic. Results: The nurses reported about the experiences they had during the pandemic, the difficulties in relation to work, how their routines were affected inside and outside of work and how this scenario triggered a series of risks for mental health Conclusion: There is an evident need for more studies on the subject, which can promote research with health institutions to provide mechanisms that reduce the impact of the SARS-CoV-2 pandemic on the mental health of nurses and other nursing professionals.